Children’s Views of SARS-CoV-2 and COVID-19 Preventive Practices: Comparing Verbal and Visual Empirical Evidence - Christidou, Vasilia; Bonoti, Fotini; Papadopoulou, Pinelopi; Hatzinikita, Vassilia; Doumpala, Polixeni (Frontiers in Education, 2022)
Despite the growing body of research on the consequences of the COVID-19 pandemic on children’s well-being, few studies so far have explored children’s points of view, while the majority were based on data collected during the first year of the pandemic. The present study attempted to capture children’s views one year after the beginning of the pandemic, and to this end, data were collected during Spring 2021 in Greece. Specifically, by combining verbal and visual data, the study attempted to explore children’s views of SARS-CoV-2 and COVID-19. Participants involved 320 children, ranging in age from 4 to 12 years, who were asked to verbally describe and draw (a) Coronavirus and (b) the preventive measures adopted to mitigate the pandemic. Data analysis indicated that overall, children’s views involve elements of scientifically appropriate information since from an early age they are able to describe and depict SARS-CoV-2 in ways that reflect the abundance of available verbal and visual information in the public sphere. Moreover, children recommended suitable COVID-19 preventive practices since their verbal and drawing responses included references to both the Hygienic and Social preventive practices that prevailed during the time of data collection. Age-related differences in children’s views, as well as differences between the two data collection techniques, were also found. Results also showed that children who described SARS-CoV-2 as a virus or a germ tended to report more hygienic practices than those who failed to describe the term appropriately. The findings shed light on the way children form their views of the novel coronavirus and COVID-19 and raise research educational implications.